Octacalcium Phosphate/Gelatin Composite (OCP/Gel) Enhances Bone Repair in a Critical-sized Transcortical Femoral Defect Rat Model. Issue 10 (30th October 2022) - Hamada, Soshi; Mori, Yu; Shiwaku, Yukari; Hamai, Ryo; Tsuchiya, Kaori; Baba, Kazuyoshi; Oizumi, Itsuki; Kanabuchi, Ryuichi; Miyatake, Naohisa; Aizawa, Toshimi; Suzuki, Osamu
Abstract: Background: Bone grafting is widely used to treat large bone defects. A porous composite of a bioactive octacalcium phosphate material with gelatin sponge (OCP/Gel) has been shown to biodegrade promptly and be replaced with new bone both in animal models of a membranous bone defect and a long bone defect. However, it is unclear whether OCP/Gel can regenerate bone in more severe bone defects, such as a critical-size transcortical defect. Questions/purposes: Using an in vivo rat femur model of a standardized, transcortical, critical-size bone defect, we asked: Compared with a Gel control, does OCP/Gel result in more newly formed bone as determined by (1) micro-CT evaluation, (2) histologic and histomorphometric measures, and (3) osteocalcin staining and tartrate-resistant acid phosphatase staining? Methods: Thirty-four 12-week-old male Sprague-Dawley rats (weight 356 ± 25.6 g) were used. Gel and OCP/Gel composites were prepared in our laboratory. Porous cylinders 3 mm in diameter and 4 mm in height were manufactured from both materials. The OCP/Gel and Gel cylinders were implanted into a 3-mm-diameter transcortical critical-size bone defect model in the left rat femur. The OCP/Gel and Gel were randomly assigned, and the cylinders were implanted. The biological responses of the defect regions were evaluated radiologically and histologically. At 4 and 8 weeks after implantation, CT evaluation, histological examination of decalcified samples, and immunostaining were quantitatively performed to evaluate new bone formation and remaining bone graft substitutes and activity of osteoblasts and osteoclast-like cells (n = 24). Qualitative histological evaluation was performed on undecalcified samples at 3 weeks postimplantation (n = 10). CT and decalcified tissue analysis was not performed blinded, but an analysis of undecalcified specimens was performed under blinded conditions. Results: Radiologic analysis revealed that the OCP/Gel group showed radiopaque regions around the OCP granules and at the edge of the defect margin 4 weeks after implantation, suggesting that new bone formation occurred in two ways. In contrast, the rat femurs in the Gel group had a limited radiopaque zone at the edge of the defect region. The amount of new bone volume analyzed by micro-CT was higher in the OCP/Gel group than in the Gel group at 4 and 8 weeks after implantation (​​4 weeks after implantation: OCP/Gel versus Gel: 6.1 ± 1.6 mm 3 versus 3.4 ± 0.7 mm 3, mean difference 2.7 [95% confidence interval (CI) 0.9 to 4.5]; p = 0.002; intraclass correlation coefficient [ICC] 0.72 [95% CI 0.29 to 0.91]; 8 weeks after implantation: OCP/Gel versus Gel: 3.9 ± 0.7 mm 3 versus 1.4 ± 1.1 mm 3, mean difference 2.5 [95% CI 0.8 to 4.3]; p = 0.004; ICC 0.81 [95% CI 0.47 to 0.94]). Histologic evaluation also showed there was a higher percentage of new bone formation in the OCP/Gel group at 4 and 8 weeks after implantation (​​4 weeks after implantation: OCP/Gel versus Gel: 31.2% ± 5.3% versus 13.6% ± 4.0%, mean difference 17.6% [95% CI 14.2% to 29.2%]; p < 0.001; ICC 0.83 [95% CI 0.53 to 0.95]; 8 weeks after implantation: OCP/Gel versus Gel: 28.3% ± 6.2% versus 9.5% ± 1.9%, mean difference 18.8% [95% CI 11.3% to 26.3%]; p < 0.001; ICC 0.90 [95% CI 0.69 to 0.97]). Bridging of the defect area started earlier in the OCP/Gel group than in the Gel group at 4 weeks after implantation. Osteocalcin immunostaining showed that the number of mature osteoblasts was higher in the OCP/Gel group than in the Gel group at 4 weeks (OCP/Gel versus Gel: 42.1 ± 6.5/mm 2 versus 17.4 ± 5.4/mm 2, mean difference 24.7 [95% CI 16.2 to 33.2]; p < 0.001; ICC 0.99 [95% CI 0.97 to 0.99]). At 4 weeks, the number of osteoclast-like cells was higher in the OCP/Gel composite group than in the Gel group (OCP/Gel versus Gel: 3.2 ± 0.6/mm 2 versus 0.9 ± 0.4/mm 2, mean difference 2.3 [95% CI 1.3 to 3.5]; p < 0.001; ICC 0.79 [95% CI 0.35 to 0.94]). Conclusion: OCP/Gel composites induced early bone remodeling and cortical bone repair in less time than did the Gel control in a rat critical-size, transcortical femoral defect, suggesting that OCP/Gel could be used as a bone replacement material to treat severe bone defects. Clinical Relevance: In a transcortical bone defect model of critical size in the rat femur, the OCP/Gel composite demonstrated successful bone regeneration. Several future studies are needed to evaluate the clinical application of this interesting bone graft substitute, including bone formation capacity in refractory fracture and spinal fusion models and the comparison of bone strength after repair with OCP/Gel composite to that of autologous bone.